Effect of mushroom powder in fresh pasta development - Correia, Paula (2017)
Fresh pastas with Shiitake mushroom flour (MF) were produced. The MF was produced by drying the mushrooms at 40, 50, and 60 ᵒC. Proportions of 5%, 10%, and 15% MF were used to prepare the fresh pastas (FP), with two types of wheat flour (regular (RWF) and 30% semolina wheat flour (SWF)). Mushroom pastas were analysed before (FP) and after cooking (CP). FP presented moisture and water acidity lower than 35% and 0.95, respectively. The L* and b* colour parameters were similar for pasta produced with RWF and SWF, with the major differences for pastas with mushroom flours obtained at 40 ᵒC and with the increasing of MF. Thus, with increasing of MF and high drying temperatures, pastas were redder, darker and less yellow. The CP showed high colour similarities between them. Generally, the introduction of MF changes the texture of pastas. Internal and external firmness, and adhesiveness, decreased with increasing MF and for higher drying temperatures. CP presented similar tendencies, with low firmness, high adhesiveness and high stickiness. The soluble solids were determined in CP cooking water, and range between 5.8 and 9.0%, without a consistent pattern, allowing classifying the pastas as high and medium quality. Sensorial analysis revealed that consumers preferred pastas produced with high content of MF with similar profiles for all the parameters tested, and the influence of the type of wheat flour was not important. It could be concluded that MP could be used to produce alternative foods, innovative and easy to cook.